2020
DOI: 10.1007/s11547-020-01203-0
|View full text |Cite
|
Sign up to set email alerts
|

It’s not over until it’s over: the chameleonic behavior of COVID-19 over a six-day period

Abstract: The current global outbreak of COVID-19 represents a major challenge in terms of epidemiology, contagiousness, treatment, as well as clinical and radiological behavior of this disease. Radiological imaging plays a key role in the diagnostic process and during the monitoring of the clinical conditions especially of patients with severe symptoms. According to the preliminary data collected in our tertiary center, we have documented a peculiar behavior in patients requiring endotracheal intubation who underwent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 9 publications
0
25
0
1
Order By: Relevance
“…The role of CXR in clinical monitoring of this patients, especially in ICU, is still debated: Fleischner Society do not recommend daily CXR in stable intubated patients, but it is also true that the disease can progress very quickly [16,17]. Our opinion is that radiological imaging should be always associated with clinical and laboratoristic parameters when monitoring the disease course, waiting for readily effective therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The role of CXR in clinical monitoring of this patients, especially in ICU, is still debated: Fleischner Society do not recommend daily CXR in stable intubated patients, but it is also true that the disease can progress very quickly [16,17]. Our opinion is that radiological imaging should be always associated with clinical and laboratoristic parameters when monitoring the disease course, waiting for readily effective therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, radiographs guarantee an adequate evaluation of the infection simultaneously optimising organisational, safety and radiation exposure issues. Regarding COVID-19, for instance, FICHERA et al [4] showed the necessity of a long-term monitoring of COVID-19 patients in intensive care unit (ICU) despite the prompt amelioration that usually occurs after intubation. Moreover, to further contribute to the management of COVID-19 patients, chest radiography-based scores, partially recalling scores proposed for previous Coronavirus epidemics such as SARS and MERS, have been proposed [8,[11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Radiological facilities are among the primary units requiring dedicated management, since radiological imaging can contribute to the diagnosis and monitoring of the disease [ 8 , 9 , 10 , 11 , 12 ]. Chest radiographs and thoracic ultrasound US are easily accessible tools available at the bedside of COVID-19 patients; nevertheless, Computed Tomography (CT) imaging may be also necessary to investigate pulmonary embolism, comorbidities, and/or to carefully evaluate the response to specific treatments [ 13 ].…”
Section: Introductionmentioning
confidence: 99%